Outbreak of Epidemic Keratoconjunctivitis Caused by Human Adenovirus Type D53 in an Eye Care Clinic — Los Angeles County, 2017 - OYong, Kelsey (MMWR Morb Mortal Wkly Rep, 2018)
On June 22, 2017, the Los Angeles County Department of Public Health (LAC DPH) was notified of seven patients who were seen at an eye care clinic on June 8, 2017, and later developed symptoms of epidemic keratoconjunctivitis (EKC). EKC is a contagious, severe form of viral conjunctivitis that can cause pain and blurred vision for up to 4 weeks (1). LAC DPH conducted an investigation, which identified 17 patients with EKC, including 15 who had visited the optometry clinic and two who were household contacts of clinic patients. Observations in the clinic found deficiencies in disinfection of tonometers (an instrument connected to a slit lamp and used to test for glaucoma by measuring intraocular pressure) and multiuse eye drop administration. Staff member education and revision of disinfection practices interrupted further transmission. Patient specimens tested positive for human adenovirus (HAdV) type D53 (HAdV-53). As the first documented EKC outbreak associated with HAdV-D53 in the United States, this outbreak highlights the need for rigorous implementation of recommended infection prevention practices in eye care settings.